Two‐step Screening for Identification of Drug‐metabolizing Bacterial Cytochromes P450 with Diversified Selectivity. Issue 6 (28th January 2020) - Hilberath, Thomas; Windeln, Leonie M.; Decembrino, Davide; Le‐Huu, Priska; Bilsing, Florestan L.; Urlacher, Vlada B.
Abstract: The evaluation of drug metabolites is compulsory during drug development. Since recently, bacterial cytochromes P450 and their mutated variants have attracted considerable interest as an alternative to hepatic P450s for the synthesis of human drug metabolites. Thus, straightforward screening approaches are required that enable rapid identification and evaluation of drug‐metabolizing bacterial P450s with different product selectivities. Herein, we report a two‐step screening method for discovery and characterization of new P450s from actinomycetes that enable oxidation of various drugs. In the first step, substrate profiling with three structurally different model drugs, ritonavir, testosterone, amitriptyline, allowed us to select CYP105D and CYP107Z from Streptomyces platensis DSM 40041 that accepted all model substrates and produced human‐like drug metabolites. In the second step, activity tests with an array of 25 structurally‐related molecules and derivatives of the three model compounds revealed a correlation between structural variations in the target drugs and the enzyme chemo‐ and regioselectivity. Abstract : Biocatalysis : A two‐step screening was developed to identify and distinguish promiscuous cytochromes P450 regarding activity and selectivity towards oxidation of chemically diverse drugs.